Román Álvarez Rodríguez, Australia y Nueva Zelanda, Un mundo al otro lado del mundo, Devonport, Auckland, 2019, 204 pp. - Balcells Doménech, José María (Estudios Humanísticos. Filología, 2020)
Resumen/abstract